2006
DOI: 10.1007/s00464-004-2265-5
|View full text |Cite
|
Sign up to set email alerts
|

Day case laparoscopic herniorraphy

Abstract: Laparoscopic herniorraphy is a safe technique suitable for day case surgery. Operator experience dictates duration of surgery. Trainees' operating times approach those of consultants after 40 procedures. Prolonged operating times and increased cost are not justifiable reasons for not recommending LH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Although we systematically assessed articles before assigning them into categories, categorization is always subject to discussion. However, only seven articles additionally reported on subjects of a category other than the one they were placed in [42,50,59,71,73,91,100]. Nonetheless, the results of these studies were consistent with the conclusions we drew for the categories they were not placed in.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Although we systematically assessed articles before assigning them into categories, categorization is always subject to discussion. However, only seven articles additionally reported on subjects of a category other than the one they were placed in [42,50,59,71,73,91,100]. Nonetheless, the results of these studies were consistent with the conclusions we drew for the categories they were not placed in.…”
Section: Discussionsupporting
confidence: 58%
“…The remaining five studies were conducted in radiology [90,91], family medicine [92,93] and anesthesiology [94]. Thirty-one studies reported no statistically significant differences between faculty and residents on a wide variety of outcomes including mortality, morbidity and length of stay [52,54,56-58,61,63,67-69,73-90,92-94]. Although patient outcomes were similar, 12 of these 31 studies did report a significantly longer operation time for residents [61,67,69,74,77,78,81,83,84,87-89].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation